Serologic evolution and follow-up to IgG antibodies of infants born to mothers with gestational COVID - Sara Vigil-Vázquez; Ángela Manzanares; Alicia Hernanz-Lobo; Itziar Carrasco-García; Clara Zamora del Pozo; Alba Pérez-Pérez; Elena María Rincón-López; Begoña Santiago-García; María del Pilar Pintado-Recarte; Roberto Alonso-Fernández; Manuel Sánchez-Luna; María Luisa Navarro-Gómez (BMC, 2023)
Abstract Background It is known that SARS-CoV-2 antibodies from pregnant women with SARS-CoV-2 infection during pregnancy cross the placenta but the duration and the protective effect of these antibodies in infants is scarce. Methods This prospective study included mothers with SARS-COV-2 infection during pregnancy and their infants from April 2020 to March 2021. IgG antibodies to SARS-CoV-2 spike protein were performed on women and infants at birth and at two and six months during follow-up. Anthropometrical measures and physical and neurological examinations and a clinical history of symptoms and COVID-19 diagnosis were collected. Simple linear regression was performed to compare categorical and continuous variables. To compare the mother's and infant's antibody titers evolution, a mixed linear regression model was used. A predictive model of newborn antibody titers at birth has been established by means of simple stepwise linear regression. Results 51 mother-infant couples were included. 45 (90%) of the mothers and 44 (86.3%) of the newborns had a positive serology al birth. These antibodies were progressively decreasing and were positive in 34 (66.7%) and 7 (13.7%) of infants at 2 and 6 months, respectively. IgG titers of newborns at birth were related to mothers' titers, with a positive moderate correlation (Pearson's correlation coefficient: 0.82, p < 0,001). Fetal/maternal antibodies placental transference rate was 1.3 (IQR: 0.7-2.2). The maternal IgG titers at delivery and the type of maternal infection (acute, recent, or past infection) was significantly related with infants' antibody titers at birth. No other epidemiological or clinical factors were related to antibodies titers. Neurodevelopment, psychomotor development, and growth were normal in 94.2% of infants in the third follow-up visit. No infants had a COVID-19 diagnosis during the follow-up period. Conclusions Transplacental transfer of maternal antibodies is high in newborns from mothers with recent or past infection at delivery, but these antibodies decrease after the first months of life. Infant's IgG titers were related to maternal IgG titers at delivery. Further studies are needed to learn about the protective role of maternal antibodies in infants.